Feasibility of Treating Hepatitis C in a Transient Jail Population. (7th July 2017) - MacDonald, Ross; Akiyama, Matthew J; Kopolow, Aimee; Rosner, Zachary; McGahee, Wendy; Joseph, Rodrigue; Jaffer, Mohamed; Venters, Homer
Abstract: Jails represent a critical component of the public health response to HCV elimination. We report on outcomes of 104 patients receiving HCV treatment from January 1, 2014 to June 30, 2016 in a large urban jail setting. Our data demonstrate that treatment in jails is feasible, but many barriers remain.